Budaya Organisasi Berbasis Inovasi dan Kinerja Karyawan dalam Industri Farmasi - Deden Abdul Wahid; Cucu Hidayat; Taurist Fathan Nasrullah; Nada Regista Yulisantina; Muhsin Muhsin (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2026)
This study presents a systematic literature review that examines the relationship between innovation-based organizational culture and employee performance in the pharmaceutical industry. The highly regulated and knowledge-based pharmaceutical industry demands innovation not only in the aspects of research and development but also in human resource management practices. Through thematic analysis of empirical and conceptual studies for the 2018-2023 period, this study identifies seven main dimensions of innovation culture that are strongly correlated with improved employee performance, namely risk tolerance, collaborative innovation, continuous learning orientation, leadership support, employee autonomy, communication openness, and special time allocation for innovation. These dimensions have been shown to drive innovative work behaviors, adaptability, and productivity of pharmaceutical employees. This research makes an important contribution to the strategic management of human resources in making the culture of innovation a mechanism to improve the performance and competitiveness of regulated organizations.